Mitochondria in Biodosimetry: Flow Cytometry Assessment in Vitro - Šinkorová, Zuzana; Lierová, Anna; Filipová, Alžběta; Čížková, Jana; Tichý, Aleš; Pejchal, Jaroslav; Milanová, Marcela; Vilasová, Zdeňka; Andrejsová, Lenka (My University, 2022)
The JC-1 dye is widely used in apoptosis studies to monitor mitochondrial health. The probe was tested in vitro on two established cell lines and peripheral porcine blood lymphocytes after gamma irradiation (IR) to assess its potential in biodosimetric evaluation. In brief, we stained irradiated and non-irradiated cells with the JC-1 dye to determine the existing changes in mitochondrial membrane potential and monitor cell health through flow cytometry. The stage of injury in these cells was evaluated through an irradiated versus non-irradiated ratio (IVNIR), comparing the relative proportion of polarised cells containing red JC-1 aggregates. We observed a decreasing IVNIR as the radiation dose increased (i.e. 0.5; 1; 2; 4; 6; 8 and 10 Gy), performing the analysis at 4, 8 and 24 h after IR in all the tested cells. The results from the JC1-dye test showed that CD4 T lymphocytes were more sensitive to irradiation than other subpopulations.
Mitochondrie v biodozimetrii: Hodnocení průtokovou cytometrií in vitro
Keywords: Mitochondria; Biodosimetry; Flow; Cytometry; Assessment; Vitro; Mitochondrie; biodozimetrie; průtoková cytometrie; posouzení; in vitro